VD_FINDINFO HC / 2011 / 119 vom 18. Februar 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, DIVORCE SUR DEMANDE UNILATÉRALE, OBLIGATION D'ENTRETIEN | 125 CC, 137 al. 2 CC, 163 al. 1 CC, 164 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)